Studi Penentuan Tarif BTS Transpakuan Koridor 5 dengan Metode ATP dan WTP - Fatihah, Anariski; Murtedjo, Tedy; Alimuddin (Indonesian Society of Applied Science, 2024)
BTS Transpakuan was officially launched on November 2, 2021, operating across 4 corridors, with the initial trial being conducted on corridor 5. Presently, it remains free, operating from 05:00 to 21:00. Notably, public interest has surged, as evidenced by a load factor of 91% recorded in September 2022. Corridor 5 stands as the sole corridor directly integrated with the KRL. The research aims to dissect the characteristics of corridor 5 BTS Transpakuan users and scrutinize tariff considerations using ATP and WTP methods. Employing an analytical-descriptive approach, primary data was gathered through questionnaires, subjected to ATP and WTP analysis, elucidating the correlation between outcomes. Of the 235 respondents utilizing corridor 5, a majority are women aged 20-30, educated up to high school level. Most are employed, earning between 2 to 3 million IDR, largely self-utilized. A transition from private vehicles to mass transit is evident, with 43 cars, 204 motorbikes, and 9 bicycles. Consequently, the current tariff stands at 3,562 IDR. An enhancement of facilities, prioritized within the tariff structure, would raise it to 4,620 IDR for a single journey. In conclusion, users' capacity to pay is outweighed by their readiness to pay, potentially increasing if facilities are enhanced.